High‐Polarizability Organic Ferroelectric Materials Doping for Enhancing the Built‐In Electric Field of Perovskite Solar Cells Realizing Efficiency over 24%. Issue 14 (27th February 2022) - Chen, Weijie; Liu, Shuo; Li, Qingqing; Cheng, Qinrong; He, Baosheng; Hu, Zhijun; Shen, Yunxiu; Chen, Haiyang; Xu, Guiying; Ou, XueMei; Yang, Heyi; Xi, Jiachen; et al.
Abstract: The built‐in electric field (BEF) intensity of silicon heterojunction solar cells can be easily enhanced by selective doping to obtain high power conversion efficiencies (PCEs), while it is challenging for perovskite solar cells (pero‐SCs) because of the difficulty in doping perovskites in a controllable way. Herein, an effective method is reported to enhance the BEF of FA0.92 MA0.08 PbI3 perovskite by doping an organic ferroelectric material, poly(vinylidene fluoride):dabcoHReO4 (PVDF:DH) with high polarizability, that can be driven even by the BEF of the device itself. The polarization of PVDF:DH produces an additional electric field, which is maintained permanently, in a direction consistent with that of the BEF of the pero‐SC. The BEF superposition can more sufficiently drive the charge‐carrier transport and extraction, thus suppressing the nonradiative recombination occurring in the pero‐SCs. Moreover, the PVDF:DH dopant benefits the formation of a mesoporous PbI2 film, via a typical two‐step processing method, thereby promoting perovskite growth with high crystallinity and a few defects. The resulting pero‐SC shows a promising PCE of 24.23% for a 0.062 cm 2 device (certified PCE of 23.45%), and a remarkable PCE of 22.69% for a 1 cm 2 device, along with significantly improved moisture resistances and operational stabilities. Abstract : An organic ferroelectric material poly(vinylidene fluoride):dabcoHReO4 as a perovskite dopant can be partially polarized by the built‐in electric field of perovskite solar cell (pero‐SC) itself, which produces an additional electric field, thus promoting the charge‐carrier transportation. A promising 24.23% power conversion efficiency (PCE) (certified PCE of 23.45%) and robust operational stability are obtained.